Pre-invasive disease pathogenesis and clinical management - Fitzgerald, Rebecca C.; SpringerLink (Online service). (New York Springer, 2011)
There are many books written on cancer, but this monograph focuses on pre-invasive disease. One of the prizes waiting to be won in cancer medicine is to thoroughly understand the processes by which a cell becomes invasive. This quest takes us into the world of stem cells and regulation of gene expression as well as to an understanding of the relative contribution of hereditary factors alongside exposures to environmental agents. This book explores these fundamental concepts as well as considering how advances in disease models combined with ?omic technologies and molecular imaging might lead to advances in treatments such as chemoprevention and endoscopic treatments. The final section of the book takes nine specific examples of pre-invasive disease and explores the current state of knowledge and clinical practice as well as looking to the future. This book is written by International experts in their field and should appeal to students and seasoned researchers, to scientists and to clinicians. No prior knowledge of the topic is required to appreciate this text and yet the book charters new territory. New perspectives are given on how our knowledge of cancer development might lead us to reconsider our clinical approach to early detection and prevention of cancer at an individual and population level.
Electronic reproduction.
Keywords: Precancerous conditions; Neoplasm invasiveness -- Pathology; Disease progression; Early detection of cancer -- Methods; Neoplasm invasiveness -- Prevention & control; Electronic books